The language of stories : a cognitive approach - Dancygier, Barbara (Cambridge : Cambridge University Press, 2012)
'How do we read stories? How do they engage our minds and create meaning? Are they a mental construct, a linguistic one or a cultural one? What is the difference between real stories and fictional ones? This book addresses such questions by describing the conceptual and linguistic underpinnings of narrative interpretation. Barbara Dancygier discusses literary texts as linguistic artifacts, describing the processes which drive the emergence of literary meaning. If a text means something to someone, she argues, there have to be linguistic phenomena that make it possible. Drawing on blending theory and construction grammar, the book focuses its linguistic lens on the concepts of the narrator and the story, and defines narrative viewpoint in a new way. The examples come from a wide spectrum of texts, primarily novels and drama, by authors such as William Shakespeare, Margaret Atwood, Philip Roth, Dave Eggers, Jan Potocki and Mikhail Bulgakov'--
'The relationship between language and literature is a contentious issue. On the one hand, it may simply be described as a relationship between raw material and a finished product - language provides the basis on which creative and unique works of literature emerge. On the other hand, once we look at meaning, the dividing lines begin to fade - it is difficult to define a sharp boundary separating the meaning of literary works and the meaning of other texts. One way of downplaying the obvious links is to claim that fiction engages knowledge much broader and culturally specific than every-day use of language does. But that would be an exaggeration. One could not follow an ordinary discussion of, say, climate change if one did not have any prior knowledge of the issue'--
Includes bibliographical references (p. 205-224) and index.
Keywords: Language and languages -- Style -- Psychological aspects; Cognitive grammar; Discourse analysis, Literary